From rejection to acknowledgement and dispute: four moments in the origins of Chilean representative democracy, 1822–1851. Issue 2 (3rd May 2020) - Casals, Marcelo; Estefane, Andrés; Ossa, Juan Luis
ABSTRACT: This article traces the changes in the meanings and uses of the concept of democracy in Chile in the period 1822–1851. Based on an extensive revision of newspapers, it shows how the idea of democracy evolved from a negative understanding of it to an increasingly positive vision that saw it as a key mechanism for legitimising political power. Essential for this transition were, first, the doctrinal disputes of the 1820s, which established a series of liberal and republican principles that ended up being constituent characteristics of Chilean democracy. Second, the concept of representation, which by normalising a way of exercising power through delegates democratically elected, allowed to cleanse democracy from what contemporaries considered its most menacing excesses. The article identifies four moments of progress and retreats of democracy during the first half of the nineteenth century, demonstrating the extent to which this was a more complex process than what is commonly believed. In so doing, it aims to question some of the general assumptions about the origins of democracy both in Latin America and Chile and to demonstrate how the acknowledgement of the idea of representative democracy was one of the main legacies of these seminal debates for nineteenth-century Chilean politics.